2019
DOI: 10.3892/etm.2019.8036
|View full text |Cite|
|
Sign up to set email alerts
|

Exogenous hydrogen sulfide protects against high glucose‑induced apoptosis and oxidative stress by inhibiting the STAT3/HIF‑1α pathway in H9c2 cardiomyocytes

Abstract: Hydrogen sulfide (H2S), an endogenous gasotransmitter, possesses multiple physiological and pharmacological properties including anti-apoptotic, anti-oxidative stress and cardiac protective activities in diabetic cardiomyopathy. An increasing body of evidence has suggested that signal transducer and activator of transcription 3 (STAT3) has beneficial effects in the heart. However, the effect of diabetes on the phosphorylation or activation of cardiac STAT3 appears to be controversial. The present study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Despite the positive results observed following the treatment of various CVDs models with H 2 S donors, the outcome mainly depends on the characteristics of the donor, cell type, and concentration used. For example, treatment with the fast-releasing donor NaHS has been reported to elevate HIF-α levels, while the slow-releasing donor GYY4137 decreases the levels [ 78 , 81 , 105 ]. Similarly, treatment with NaHS has been shown to sulfurate and increase the activities of c-jun/AP-1 in macrophages [ 124 ], while inhibition of the JNK pathway has been reported in cardiomyocytes and epithelial cells A549 [ 104 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the positive results observed following the treatment of various CVDs models with H 2 S donors, the outcome mainly depends on the characteristics of the donor, cell type, and concentration used. For example, treatment with the fast-releasing donor NaHS has been reported to elevate HIF-α levels, while the slow-releasing donor GYY4137 decreases the levels [ 78 , 81 , 105 ]. Similarly, treatment with NaHS has been shown to sulfurate and increase the activities of c-jun/AP-1 in macrophages [ 124 ], while inhibition of the JNK pathway has been reported in cardiomyocytes and epithelial cells A549 [ 104 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…In smoke-induced left ventricular dysfunction rat models, treatment with NaHS suppresses the elevated pro-apoptotic activities by activating the PI3K/AKT and deactivating the c-jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK) pathways [ 104 ]. In addition, it has been shown that treatment with GYY4137 can markedly prevent glucose-induced damage in H9c2 cells by reducing apoptosis via the inhibition of the STAT-3/HIF-α signaling cascade [ 105 ]. Collectively, the above evidence indicates that apoptosis-induced progression of myocardial dysfunction can be attenuated with the elevation of H 2 S levels.…”
Section: Role Of H 2 S In Vascular Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 S can act as a signal molecule immediately after it is released, and it can also be stored as bound endosulfan, which can release H 2 S. At physiological pH, nearly two-thirds of H 2 S is in the form of hydrogen sulfide anion (HS–) (Guo et al, 2016 ). H 2 S plays important roles in many physiological processes, including vasodilation, blood pressure reduction (Greaney et al, 2017 ; Jin et al, 2017 ), anti-apoptosis (Li et al, 2019b ), anti-inflammation (Zhao et al, 2019 ), anti-oxidative stress (Tocmo and Parkin, 2019 ), cell survival/death, cell differentiation, cell proliferation/hypertrophy, mitochondrial bioenergetics/biogenesis, and endoplasmic reticulum stress (ERS) ( Figure 1 ) (Zhang D. et al, 2017 ). Recent studies have shown that H 2 S ameliorates diabetic complications including endothelial dysfunction (Li et al, 2019a ), nephropathy (Karmin and Siow, 2018 ), retinopathy (Wang P. et al, 2019 ), and cardiovascular diseases (Citi et al, 2018 ).…”
Section: Overview Of H 2 Smentioning
confidence: 99%
“…In addition, recent studies demonstrated that H 2 S, in the form of a NaHS donor, may reduce high glucose-induced oxidative stress, inflammation, and apoptosis by activating the Nrf2/ARE pathway and may exert anti-apoptotic effects in diabetic myocardium by inhibiting c-Jun N-terminal kinase (JNK) and p38 MAPK pathways and activating PI3K/Akt signaling in vitro and in vivo [ 266 ]. Nevertheless, other recent studies showed that slow-releasing H 2 S donor, GYY4137, induces cardioprotection against myocardial ischemia and reperfusion injury by attenuating oxidative stress and apoptosis via activation of the PHLPP-1/Akt/Nrf2 pathway in mice [ 267 ], inhibition of the STAT3/HIF-1α signaling pathway [ 268 ], and activation of the AMPK (5′AMP-activated protein kinase)/mTOR signal pathway in high glucose-induced H9c2 cardiomyocyte damage [ 269 ]. Moreover, the GYY4137 donor exerts anti-inflammatory effects by suppression of the NF-kB and MAPK signaling pathway in Coxsackie virus B3-infected rat cardiomyocytes [ 270 ] as well as attenuating the development of diabetic cardiomyopathy via FoxO1 signaling pathway in vitro and in vivo [ 271 ].…”
Section: H 2 S Redox Signaling and Resiliencementioning
confidence: 99%